An Evolution in Intercultural Studies: Introducing Intercultural Communication Needs Model and Triple Needs Theory in English Language Teaching [In English] - Vahid Ghorbani; Hamid Reza Dowlatabadi (زبان کاوی کاربردی)
Developing a new model and theory along with key macro-elements in intercultural studies was a big gap and problem for more than a decade. The current study filled this gap by introducing the intercultural communication needs model (ICN) and Triple Needs Theory (TNT). Thus, the researchers selected 100 participants to partake in this study to collect the required data. 20 participants out of 100 willingly took part in interview sessions, too. The researchers used a mixed methods design and complex quantitative and qualitative methods such as exploratory and confirmatory factor analysis along with inductive content analysis to collect and analyze the data to develop the model and theory. The results showed that The ICN model and triple needs theory (TNT) introduce language, emotion, and culture as the newest macro-elements of intercultural interactions. Also, the results revealed that contextual and individual factors influence the priority and selection of these three needs: language, emotion, and culture. This study is of high significance for language instructors, intercultural and cultural psychologists, and politicians in that it helps them to ameliorate the quality and effectiveness of their instruction, therapy, and political meetings respectively.